Adsorption behaviors of atrazine and imidacloprid on high temperature aged microplastics: Mechanism and influencing factors - Hong-yan Wu; Qian-yin Yuan; Bo Chen; Qiao-ping Kong; Shuang-shuang Huang; Lin Cheng; Shu-hui Wang; Jian-jun Lian (Desalination and Water Treatment)
The migration behavior of pesticides in water under the coexistence of microplastics is not sufficiently known. In this study, the effects of main environmental factors on the adsorption characteristics of atrazine (ATZ) and imidacloprid (IMD) on aged polyethylene (PE) microplastics in aqueous solution were investigated, and the adsorption mechanisms were also discussed. The results showed that the pseudo-first-order and Freundlich models fitted the adsorption kinetics and isotherms of ATZ and IMD on PE well. The adsorption capacity of PE toward ATZ and IMD could be reached to as high as 350.40 μg/g and 327.75 μg/g, respectively, at 298 K and pH 7. Moreover, the adsorption process of the two pesticides was a spontaneous and endothermic process. The removal amount of ATZ by PE was highest at pH= 3, and the removal rate decreased with the increasing of pH; while the removal rate of IMD by PE was best under neutral conditions. The increase in HA concentration reduced the adsorption capacity of ATZ (4.79–57.2 %) and IMD (3.94–30.02 %). Besides, the main adsorption mechanism of ATZ and IMD was hydrophobic interaction. This study provides a theoretical reference for investigating the effects of aging microplastics on the migration behavior of different pesticides in water environments.